FeIII and FeII Phosphasalen Complexes: Synthesis, Characterization, and Catalytic Application for 2‐Naphthol Oxidative Coupling. Issue 60 (30th September 2020) - Oheix, Emmanuel; Herrero, Christian; Moutet, Jules; Rebilly, Jean‐Noël; Cordier, Marie; Guillot, Régis; Bourcier, Sophie; Banse, Frédéric; Sénéchal‐David, Katell; Auffrant, Audrey
Abstract: We report on the synthesis and characterization of three iron(III) phosphasalen complexes, [Fe III (Psalen)(X)] differing in the nature of the counter‐anion/exogenous ligand (X − =Cl −, NO3 −, OTf − ), as well as the neutral iron(II) analogue, [Fe II (Psalen)] . Phosphasalen (Psalen) differs from salen by the presence of iminophosphorane (P=N) functions in place of the imines. All the complexes were characterized by single‐crystal X‐ray diffraction, UV/Vis, EPR, and cyclic voltammetry. The [Fe II (Psalen)] complex was shown to remain tetracoordinated even in coordinating solvent but surprisingly exhibits a magnetic moment in line with a Fe II high‐spin ground state. For the Fe III complexes, the higher lability of triflate anion compared to nitrate was demonstrated. As they exhibit lower reduction potentials compared to their salen analogues, these complexes were tested for the coupling of 2‐naphthol using O2 from air as oxidant. In order to shed light on this reaction, the interaction between 2‐naphthol and the Fe III (Psalen) complexes was studied by cyclic voltammetry as well as UV/Vis spectroscopy. Abstract : Phosphasalen iron(II) and iron(III) complexes, that differ from their salen analogues by the presence of a P=N linkage instead of imine in the ligand backbone, were synthesized and characterized in the solid state and in solution. The Fe III complexes were used to catalyze the oxidative coupling of 2‐naphthol using O2 from air as oxidant.